Interreligious Violent Conflict Resolution: Discoursing Communal Violence between Christians and Moslems in Poso City, Indonesia - Destin Nurafiati Ristanti (Hasanuddin University, 2022)
After the reformation occurred in 1998, the political situation in Indonesia became unstable. Military forces had been concentrated in the central government to maintain stability. Thus, the situation in Indonesia became vulnerable and easy to be provoked. During that period, various conflicts happened and escalated, such as ethnic and interreligious group conflicts. One of those conflicts occurred in Poso, considered one of the most violent conflicts in Indonesia after the reformation. It was an interreligious conflict between the Christian and Muslim groups in Poso, a city in Central Sulawesi. In this city, the interreligious conflict between these two groups took place a few times through some phases, involving both militant and violent groups. The conflict was eventually settled through the dialogue between two conflicting groups, each led by respected religious local figures. The government mediated the dialogue through one of the public officials who was respected in the country. In the last stage of Poso conflict resolution, Malino Declaration was set to end the conflict, and the military was sent to the city to keep the peace process, and the conflict perpetrators were sent to trial.